2018
DOI: 10.1186/s12964-018-0290-6
|View full text |Cite
|
Sign up to set email alerts
|

Autologous blood transfusion augments impaired wound healing in diabetic mice by enhancing lncRNA H19 expression via the HIF-1α signaling pathway

Abstract: BackgroundImpaired wound healing frequently occurs in diabetes mellitus (DM) and is implicated in impaired angiogenesis. Long non-coding RNA (lncRNA) H19 has been reported as being reduced in DM and played a critical role in inducing angiogenesis. Thus, we hypothesized that H19 may affect impaired wound healing in streptozotocin (STZ)-induced diabetic mice transfused with autologous blood preserved in standard preservative fluid or modified preservative fluid.MethodsFibroblasts in injured skin were isolated an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 45 publications
0
32
0
Order By: Relevance
“…24 A previous study conducted by Chen et al demonstrated that lncRNA H19 expression is enhanced in diabetic mice. 25 FBN1, a 350-kDa glycoprotein, has been emphasized to be involved in the establishment of elastic fibers or micro-fibrils delivering strength and flexibility to connective tissues. 26 FBN1 was F I G U R E 5 Silencing of lncRNA H19 impedes wound healing in DFU mice.…”
Section: Discussionmentioning
confidence: 99%
“…24 A previous study conducted by Chen et al demonstrated that lncRNA H19 expression is enhanced in diabetic mice. 25 FBN1, a 350-kDa glycoprotein, has been emphasized to be involved in the establishment of elastic fibers or micro-fibrils delivering strength and flexibility to connective tissues. 26 FBN1 was F I G U R E 5 Silencing of lncRNA H19 impedes wound healing in DFU mice.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of HIF‐lα in reinjected allogeneic blood cells has been demonstrated to enhance the healing of wounds in diabetic mice, while acting to induce the angiogenesis and infiltration of macrophages in the wound beds; VEGF‐A induced by macrophages has also been shown to accelerate angiogenesis . Recent studies have revealed that the HIF‐lα pathway activation underlay the promotive effects of H19 on the activation of fibroblasts, as well as augmenting the effects associated with transfusion with improved autologous blood on the postoperative wound healing in diabetic mice . Existing literature has suggested that Ft1 promotes angiogenesis through HIF‐1α‐triggered expression and secretion of VEGF.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically, they showed that H19 increased the expression of the angiogenic protein HIF-1α in fibroblasts by methylating histones via H3K4me3. 28 Another transfusion study by Liu et al investigated the effects of autologous blood transfusions on wound healing in a similar diabetic mouse model. Mice treated with autologous blood efficacious in speeding wound healing showed increased levels of lncRNA MALAT1, which was found to activate fibroblasts through the initiation of the HIF-1α signaling pathway.…”
Section: Integumentary Systemmentioning
confidence: 99%
“…Guo et al utilized autologous blood transfusions in a streptozocin‐induced diabetic mouse model in which lncRNA H19 was upregulated, improving wound healing. Mechanistically, they showed that H19 increased the expression of the angiogenic protein HIF‐1α in fibroblasts by methylating histones via H3K4me3 28 . Another transfusion study by Liu et al investigated the effects of autologous blood transfusions on wound healing in a similar diabetic mouse model.…”
Section: Therapeutic Activity Of Lncrna For Tissue Repair and Regenermentioning
confidence: 99%